ACADEMIC IMPACT AND VISIBILITY OF RESEARCH ON SEMANTIC WEB: analyzing citations and online attention - Araujo, Ronaldo Ferreira de; Santarem Segundo, Jose Eduardo [UNESP]; Travieso-Rodriguez, Crispulo; Caran, Gustavo Miranda (Univ Federal Campina Grande, 2021)
This study is focused on Semantic Web and based on the analysis of production and impact of published research, according to bibliometric indicators of citation, altmetrics indicators of online attention and their correlation. Using data from 5.000 scientific papers by Dimensions database published from 2014 to 2019, it was found that the main subject area was Information and Computing Science, which gathered 79% of the total sample. Attending to co-occurrence of terms, the principal cluster identified proves the relevance of discussion topics on the structure for developing the semantic web. As a whole, it was counted 14.945 cites regarded to academic impact, and 3.929 mentions in social media regarding online attention. Correlation coefficient referred to citation and altmetrics showed weak linear relationships for most of the variables, except for Mendeley (p-value = 0,73). Finally, it is underlined the need to combine both bibliometrics and altmetrics methods and the convenience of carrying out qualitative approaches that explain their mutual relationships.
Keywords: Semantic Web; Bibliometrics; Altmetrics; Citation analysis; Online attention